Assessment of genetic diversity among wheat (Triticum aestivum L.) cultivars from a range of localities across Pakistan using random amplified polymorphic DNA (RAPD) analysis - Muhammad Shahid Mukhtar; Mehboob-ur Rahmanw; Yusuf Zafar (Euphytica, 2002)

Individual and combined effect of waterlogging and salinity on crop yields in the Indus basin - Muhammad Akram Kahlown; Muhammad Azam (Irrigation and Drainage, 2002)
Waterlogging and salinity are the major threats to the sustainability of irrigated agriculture in Pakistan. About 50% of the Culturable Command Area (CCA) in the Fordwah Eastern Sadiqia South (FESS) is affected by waterlogging and 12% by surface and profile salinity. A sample of 26 watercourses was selected in the project area to evaluate the individual and combined impacts of waterlogging and salinity on the yields of cotton, wheat, sugarcane and rice. The crop yields were measured separately for waterlogged fields and those affected with salinity and waterlogging simultaneously. The extent of yield loss as result of a rise in the water table from 1–2 m to less than 1 m was 27 and 33% for wheat and sugarcane crops, whereas it was 7 and 6% in the case of a drop of the water table to more than 2 m. For cotton, a rising water table from 2–3 m to 1–2 m and less than 1 m gave a yield decrease of about 11 and 60% respectively. The rice crop preferred waterlogging, and in contrast to other crops, gave about 7% less yield with a lowering of the water table from less than 1 m to 1–2 m. The wheat and sugarcane yields had decreasing trends with salinity in excess of 4 dS m −1 and had complete failures with salinity greater than 12 dS m −1 at water table depths of less than 1, 1–2 and 2–3 m. The cotton crop demonstrated relatively higher salinity tolerance under a water table deeper than 1 m. However, this crop could not survive at salinity levels in excess of 12 dS m −1 at water table depth of less than 1 m. The rice crop was a complete failure at salinity level of greater than 12 dS m −1 under water table depths of less than 1 and 1–2 m. The combined impact of waterlogging and salinity was more harmful to crop yields when compared with the individual effects of waterlogging. The combined analysis of waterlogging and salinity on crop yields provide a good sensitivity of the salinity‐yield relationships and indicated the importance of subsurface drainage. Copyright © 2002 John Wiley & Sons, Ltd.

Geochemical Behavior of Arsenic in Kelly Lake, Ontario - Muhammad Sadiq; Allen Locke; Grame Spiers; David A. B. Pearson (Water, Air, & Soil Pollution, 2002)

Response of three wheat genotypes grown under saline medium to low/high potassium levels - M. U. Shirazi; B. Khanzada; Muhammad Ali; Ejaz ul Islam; S. M. Mujtaba; R Ansari; S. M. Alam; M. A. Khan; Mukhtiar Ali (Acta Physiologiae Plantarum, 2002)

Drug release from kollicoat SR 30D-coated nonpareil beads: Evaluation of coating level, plasticizer type, and curing condition - Zezhi J. Shao; Luis Morales; Steven Diaz; Nouman A. Muhammad (AAPS PharmSciTech, 2002)

Linkage analysis identifies the thyroglobulin gene region as a major locus for familial congenital hypothyroidism - Bodil Ahlbom; Muhammad Yaqoob; Peter Gustavsson; Hafez Abbas; Göran Annerén; Agne Larsson; Claes Wadelius (Human Genetics, 2002)

Genetic relationship in Vigna mungo (L.) Hepper and V. radiata (L.) R. Wilczek based on morphological traits and SDS-PAGE - Abdul Ghafoor; Zahoor Ahmad; Afsari Sharif Qureshi; Muhammad Bashir (Euphytica, 2002)

Lentiviral expression of HIV-1 Vpr induces apoptosis in human neurons - Charvi A Patel; Muhammad Mukhtar; Stephen Harley; Joseph Kulkosky; Roger J Pomerantz (Journal of NeuroVirology, 2002)